Toll-Like Receptor 4 in the Rat Caudal Medulla Mediates Tooth Pulp Inflammatory Pain - Filippini, Helena F.; Molska, Graziella R.; Zanjir, Maryam; Arudchelvan, Yamini; Gong, Siew-Ging; Campos, Maria M.; Avivi-Arber, Limor; Sessle, Barry J. (Frontiers in Neuroscience, 2020)
The aims of this study were to investigate if Toll-like receptor 4 (TLR4) is expressed in the medullary dorsal horn (MDH) and if medullary application of a TLR4 antagonist (lipopolysaccharides from Rhodobacter sphaeroides, LPS-RS) can attenuate changes in nociceptive sensorimotor responses or TLR4 expression that might be evoked by mustard oil (MO) application to the right maxillary first molar tooth pulp. Of 41 adult male Sprague-Dawley rats used in the study, 23 received intrathecal application of the TLR4 antagonist LPS-RS (25 μg/10 μl; LPS-RS group) or isotonic saline (10 μl; vehicle control group) 10 min before pulpal application of MO (95%; 0.2µl). Bilateral electromyographic (EMG) activities of the anterior digastric and masseter muscles were recorded continuously before and until 15 min after the MO application to the pulp. In 6 of these 23 rats and an additional 18 rats, the caudal medulla containing the ipsilateral and contralateral MDH was removed after euthanasia for subsequent Western Blot analysis of TLR4 expression in LPS-RS (n= 8) and vehicle (n=8) groups and a naïve group (n=8). The % change from baseline in the MO-evoked EMG activities within the anterior digastric muscles were significantly smaller in the LPS-RS group than the control group (two -way ANOVA, post-hoc Bonferroni, P ˂ 0.0001). Western Blot analysis revealed similar levels of TLR4 expression in the caudal medulla of the naïve, vehicle and LPS-RS groups. These novel findings suggest that TLR4 signaling in the caudal medulla may mediate MO-induced acute dental inflammatory pain in rats.